Discovery of 4-arylthiophene-3-carboxylic acid as inhibitor of ANO1 and its effect as analgesic agent - Yuxi Wang; Jian Gao; Song Zhao; Yan Song; Han Huang; Guiwang Zhu; Peili Jiao; Xiangqing Xu; Guisen Zhang; Kewei Wang; Liangren Zhang; Zhenming Liu (Elsevier, 2021)
Anoctamin 1 (ANO1) is a kind of calcium-activated chloride channel involved in nerve depolarization. ANO1 inhibitors display significant analgesic activity by the local peripheral and intrathecal administration. In this study, several thiophenecarboxylic acid and benzoic acid derivatives were identified as novel ANO1 inhibitors through the shape-based virtual screening, among which the 4-arylthiophene-3-carboxylic acid analogues with the best ANO1 inhibitory activity were designed, synthesized and compound 42 (IC50 = 0.79 μmol/L) was finally obtained. Compound 42 selectively inhibited ANO1 without affecting ANO2 and intracellular Ca2+ concentration. Subsequently, the analgesic effect was investigated by intragastric administration in pain models. Compound 42 significantly attenuated allodynia which was induced by formalin and chronic constriction injury. Through homology modeling and molecular dynamics, the binding site was predicted to be located near the calcium-binding region between α6 and α8. Our study validates ANO1 inhibitors having a significant analgesic effect by intragastric administration and also provides selective molecular tools for ANO1-related research.